Age-related traumatic anatomy and personalized medial incision design for calcaneal fractures in older adults using three-dimensional mapping - Yuanzhen Zhang; Jiayun Liu; Jinhua Yang; Ye Yuan; Guoyong Yin; Yu Zhang; Chun Lu (Journal of Orthopaedic Surgery and Research)
Abstract Background Calcaneal fractures usually arise from high-energy trauma and predominantly impact young individuals. In older adults (aged ≥ 50 years), declining bone density and muscle strength increase fracture risk from low-energy trauma, leading to a bimodal epidemiological distribution. The intricacies of calcaneal fractures in older adults, alongside osteoporosis and soft tissue fragility, complicate surgical intervention. This study aims to analyze age-related differences in calcaneal fracture characteristics using three-dimensional(3D) mapping and assess their impact on medial incision design. Method A total of 95 patients with closed calcaneal fractures were categorized into two groups: Younger (< 50 years, n = 61) and Older (≥ 50 years, n = 34). The process of 3D fracture mapping was executed utilizing Mimics and 3-matic software, alongside the reconstruction of soft tissue, which encompassed the posterior tibial neurovascular bundle. Differences in fracture distribution and incision parameters (length, α angle, D1, and D2) were statistically analyzed, with p < 0.05 considered statistically significant. Results Fracture lines in both groups were predominantly located around the lateral Gissane’s angle and critical weight-bearing areas of the calcaneus. In the Younger Group, fracture lines were long, continuous, and involved fewer fragments, correlating with high-energy trauma. The Older Group showed more comminuted lines, characteristic of osteoporotic fractures. The α angle and D1 distance were significantly smaller in the Older Group (p < 0.05), indicating closer proximity to the medial malleolus. D2 values were also smaller (p < 0.05), with 48.65% intersecting the neurovascular bundle compared to 31.34% in the Younger Group. Conclusion Age significantly influences medial wall fracture patterns and complexity in calcaneal injuries. A personalized medial incision based on fracture morphology provides better exposure and reduction compared to traditional methods. Although the incision is closer to the neurovascular bundle in older patients, meticulous surgical technique guarantees safety. The integration of a medial incision with sinus-tarsi (ST) approach minimizes the necessity for extensive lateral exposure, thereby diminishing soft tissue complications and improving surgical outcomes for the elderly population. Level of evidence Level IV, retrospective case series.